Perbandingan Sistem Hukum Civil Law - jannah, nur; Syarifa Aini; Mhd.Ilham Hidayat Rastami; Sri Hadiningrum (Lembaga Pengembangan Kinerja Dosen, 2024)
The third source of law referred to in the civil law system is jurisprudence. When argued that customary law applies to all members of society as a whole not directly, but through jurisprudence. However, the position of jurisprudence as legal sources in the civil law system have not long been accepted. This was caused by the view that rules of conduct, especially statutory rules, are aimed at to regulate the existing situation and avoid conflict, thus the rules made for matters after the law was enacted. Law in p This is a guideline regarding what can and cannot be done. The forms of legal sources in the formal sense in the Civil Law legal system are: Legislation, customs and jurisprudence. Countries Civil law adherents place the constitution at the highest level in the hierarchy of regulations Legislation